60 Utility of t wave amplitude as a non-invasive risk marker of sudden cardiac death in hypertrophic cardiomyopathy. (5th October 2017) - Sugrue, A; Killu, AM; DeSimone, CV; Chahal, AA; Vogt, JC; Kremen, V; Hai, J; Hodge, DO; Acker, NG; Geske, JB; Ackerman, MJ; Ommen, SR; et al.
Abstract : Objective: Sudden cardiac arrest (SCA) is the most devastating outcome in hypertrophic cardiomyopathy (HCM). Presently, risk stratification is imperfect and underscores the need to identify novel markers for malignant disease. We evaluated repolarization features on the surface electrocardiograms (ECG) to identify potential risk factors for SCA. Methods: Data was collected from 52 HCM patients who underwent implantable cardioverter defibrillator (ICD) implantation. Leads V2 and V5 from the ECG closest to the time of ICD implant were utilized for measuring the Tpeak-Tend interval (Tpe), QTc, Tpe/QTc, T-wave duration, and T-wave amplitude. The presence of the 5 traditional SCA-associated risk factors was assessed, as well as the HCM risk-SCD score. Results: 16 (30%) patients experienced aborted cardiac arrest over 8.5±4.1 years, with 9 receiving an ICD shock and 7 receiving ATP. On univariate analysis, T-wave amplitude was associated with appropriate ICD therapy (HR per 0.1 mV 0.79, 95% CI 0.56–0.96, p=0.02). Aborted SCA was not associated with a greater mean QTc duration, Tpeak-Tend interval, T-wave duration, or Tpe/QT ratio. Multivariate analysis (adjusting for cardinal HCM SCA-risk factors) showed T-wave amplitude in Lead V2 was an independent predictor of risk (adjusted HR per 0.1 mV 0.74, 95% CI 0.57–0.97, p =0.03). Addition of T-wave amplitude in Lead V2 to the traditional risk factors resulted in significant improvement in risk stratification (C-statistic from 0.65 to 0.75) but did not improve the performance of the HCM SCD-risk score. Conclusion: T-wave amplitude is a novel marker of SCA in this high risk HCM population and may provide incremental predictive value to established risk factors. Further work is needed to define the role of repolarization abnormalities in predicting SCA in HCM.